Forward-backward systems for expected utility maximization - Ulrich Horst; Ying Hu; Peter Imkeller; Anthony Réveillac; Jianing Zhang (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
In this paper we deal with the utility maximization problem with a general utility function. We derive a new approach in which we reduce the utility maximization problem with general utility to the study of a fully-coupled Forward-Backward Stochastic Differential Equation (FBSDE).
Keywords: C61; D52; D53; 330; Erwartungsnutzen; Mathematische Optimierung; Analysis; Stochastischer Prozess; Theorie